2019
DOI: 10.1097/wnf.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as Add-On to Antipsychotic Treatment in Patients With Chronic Schizophrenia: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Background Introduction of old and new generations of antipsychotics leads to significant improvements in the positive symptoms of schizophrenia. However, negative symptoms remain refractory to conventional trials of antipsychotic therapy. Recently, there were several open clinical human trials with curcumin. Curcumin is a natural polyphenol, which has a variety of pharmacological activities, including antioxidative and neuroprotective effects. The studies showed that curcumin improved the negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 40 publications
0
29
0
3
Order By: Relevance
“…Curcumin is a plant alkaloid obtained from Curcuma longa with potent anti‐inflammatory and antioxidant effects. In addition, curcumin has shown neuroprotective effects in animal models of Alzheimer's disease (Mishra & Palanivelu, ), Parkinson's disease (Mythri & Bharath, ), and schizophrenia (Miodownik et al, ). The antidepressant effects of curcumin have been explored in different animal models, which act through lowering inflammation, protecting against oxidative stress, and modulating the release of serotonin and dopamine.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a plant alkaloid obtained from Curcuma longa with potent anti‐inflammatory and antioxidant effects. In addition, curcumin has shown neuroprotective effects in animal models of Alzheimer's disease (Mishra & Palanivelu, ), Parkinson's disease (Mythri & Bharath, ), and schizophrenia (Miodownik et al, ). The antidepressant effects of curcumin have been explored in different animal models, which act through lowering inflammation, protecting against oxidative stress, and modulating the release of serotonin and dopamine.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Of the 367 participants, 68.9% (253/367) sought help; of those, 64.6% (n=163) pursued professional psychiatric services and 30.8% (n=78) pursued non-medical options (i.e., relatives, praying to Buddha) as the most common first choices. (2) The help-seeking behavior ratio (seeking help individuals/total sample size) is significantly lower in the illiterate group than in other education levels. Those with a family history of mental disorders tend to have a higher help-seeking behavior ratio.…”
Section: Resultsmentioning
confidence: 92%
“…Schizophrenia (SZ) is a chronic, recurrent and severe mental disorder prevailing in about 0.63% to 0.94% of the population (with an average annual rate of 0.81%) [1].Most people with SZ benefit from antipsychotic treatment [2]with early diagnosis being critical. Unfortunately, many individuals with SZ avoid getting help, estimates of 20% to 70% do not seek for help worldwide as shown in previous studies [3].…”
Section: Introductionmentioning
confidence: 99%
“…MLN2238, a proteasome inhibitor, and Curcumin, the active anti-inflammatory ingredient in turmeric, were the top compounds projected to reverse the E2-withdrawal DEG signature ( Figure S9B ), with Curcumin comprising 5 of the top 50 hits to the database. Curcumin has a growing literature that suggests it can decrease anxiety or alleviate depression-like symptoms in animal models for depression 68 , 69 , neurological disease 70 , and schizophrenia 71 . A recent meta-analysis of several studies on curcumin, including placebo-controlled trials, concluded that curcumin is safe and effective in helping alleviate symptoms of depression in patients 72 .…”
Section: Discussionmentioning
confidence: 99%